The changing public/private mix in the American Health Care System - Mirella Cacace (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2007)
This paper discusses the fundamental changes in the American health care system during the past four decades. By applying a multidimensional framework, the changing role of the state in financing, service provision, and in the regulation of the health care system are scrutinized. The results suggest a considerable blurring of the private, market based health care system of the United States. While the state constantly retreats from service provision, it substantially intensifies its engagement in financing and also in the regulation of the system. The most path-breaking changes in regulation, however, are observed through the introduction of managed care, which, from a private market side, brought new elements of hierarchical coordination into the system.
Keywords: 330; Gesundheitswesen; Gesundheitsfinanzierung; Public-Private Partnership; Managed Care; USA